Characteristics of Serially Propagated Monkey Kidney Cell Cultures with Persistent Rubella Infection - Maassab, H. F. (1966)
Maassab, H. F. (University of Michigan, Ann Arbor), and J. A. Veronelli. Characteristics of serially propagated monkey kidney cell cultures with persistent rubella infection. J. Bacteriol. 91:436–441. 1966.—A persistent infection of LLC-MK(2) cells with rubella virus has been established and maintained for over 3 years. This “carrier culture,” designated as LLC-MK(2)-RAL, possesses distinct morphological and biological characteristics when compared with the original uninfected LLC-MK(2) line. The mechanism of viral persistance has not been entirely elucidated, but available data suggest a regulated infection with transmission of the virus directly from cell to cell or through cell division. Interferon was isolated from RAL (rubella-associated line) culture, which explains partly the wide spectrum of resistance to superinfecting viruses. Amantadine, although inhibiting cultures of LLC-MK(2) cells infected with rubella virus, failed to cure the “carrier culture.”